Defining success factors to describe coordinated care in cancer. Issue 3 (23rd May 2018) - Shaw, Tim; York, Sarah; White, Kahren; McGregor, Deborah; Rankin, Nicole; Hawkey, Alex; Aranda, Sanchia; Rushton, Shelley; Currow, David
Abstract: Providing coordinated care remains a challenge for cancer services globally. There is a lack of consensus in the literature about what constitutes successful coordinated care. This study aimed to define and prioritize a set of consensus-driven success factors that can lead to coordinated care. A mixed-methods approach was used that included literature review, a broad call for submissions from relevant stakeholders, and a priority-setting process based on a modified nominal group technique. Thirty articles that related to success factors in coordinated care were identified in the literature. Twenty submissions were received from a broad range of stakeholders. From these sources, a set of 20 success factors was derived. Seventy stakeholders attended a series of workshops across New South Wales, Australia, to review and prioritize these 20 success factors against significance and measurability. Clear consensus was reached on prioritizing two success factors linked to improving coordinated care from first presentation to diagnosis and ensuring that patients are routinely screened for physical and supportive care needs. Other highly ranked factors included the need for a comprehensive care plan and the identification of patients at higher risk for disjointed care. This study defines and prioritizes a set of success factors related to coordinated care in cancer. These success factors will be used to guide the development of interventions that target improving coordinated care as well as supporting the development of new funding models based on performance indicators derived from these factors. Abstract : Coordinating care from first presentation to diagnosis and screening patients for psychosocial distress and supportive care needs were identified as key factors in coordinated care for patients with cancer.